Detection of enterovirus in cerebrospinal fluids without pleocytosis in febrile infants under 3 months old reduces antibiotherapy duration - Blachez, Marion; Boussier, Jeremy; Mariani, Patricia; Caula, Caroline; Gaschignard, Jean; Lefèvre-Utile, Alain (Frontiers in Pediatrics, 2023)
Background: Infants under 3 months old with fever often receive empirical antibiotic treatment. Enterovirus is one of the leading causes of infection and aseptic meningitis but is not systematically screened. We aimed to evaluate enterovirus positive RT-PCR proportion in cerebrospinal fluid (CSF) with no pleocytosis and its impact on antibiotic treatment duration. Methods: During the enterovirus endemic season, from 2015 to 2018, we retrospectively studied infants under 3 months old, consulting for fever without cause, with normal CSF analysis, and receiving empirical antibiotic treatment. Clinical and biological data were analyzed, notably enterovirus RT-PCR results. The primary outcome was the duration of antibiotic therapy. Results: 92 patients were recruited. When tested, 41% of infants were positive for enterovirus, Antibiotic duration was reduced in enterovirus positive in comparison to negative patients with respectively 1.9 [1.7–2] vs 4.1 [2–6], p <0,001. No clinical nor biological features differed according to the enterovirus status. Conclusion: In this population, enterovirus positive CSF are frequent despite the absence of pleocytosis. However, its research was not guided by clinical or biological presentations. Systematic and routine use of enterovirus RT-PCR during enterovirus season, regardless of CSF cell count, could reduce the prescription of antibiotics in febrile infants under 3 months old without clinical orientation.